A multi-criteria analysis framework for conflict resolution in the case of offshore wind farm sitting: A study of England and the Netherlands offshore space - Guşatu, Laura Florentina; Zuidema, Christian; Faaij, André (Frontiers in Marine Science, 2022)
Growing EU energy ambitions in the North Sea region are urging for an accelerated deployment of large-scale renewable energy (RE) infrastructure, with offshore wind farms (OWF) playing an essential role. However, implementing the current EU targets is limited by the competing spatial claims between existing sea uses and OWFs and uncertainties related to potential risks of interaction, creating important barriers to a swift roll-out of RE infrastructure. In tackling this issue, we are proposing a transparent and spatially explicit multi-criteria analysis tool to quantify and qualify the main risks and opportunities resulting from the interaction between OWFs and four other seas user groups (shipping, marine protected areas, fisheries and military activities). The multi-criteria analysis framework is accounting for sectoral activity specific risks of interaction with OWFs, classified through the respective available conflict resolution options, which allows for the quantification of the average conflict score (ACS) between the selected activities and OWFs. Using the resulting ACS and the geo-location of areas of interaction, we map areas of high and low conflict with OWFs and indicate management options for solving, minimizing or compensating the conflicts. Our results indicate that conflict resolution strategies in marine mammal’s habitats present the highest potential for unlocking medium value OWF sites both for the Dutch case (15.8 – 28 GWs) and English case (15.94-28.3 GWs), followed by pelagic fisheries in the Dutch case (15-26.9 GWs) and passenger/cargo routes in the English case (10.9-19.4 GWs). The strategic planning of increasingly larger and more complex OWF projects will require a better understanding not only of the level of conflict with the other sea users in relation to the valuable OWF sites, but also potential management options to solve, minimize or compensate those conflicts. As an example, accessing 6.8-12.3 GWs in high value OWF sites in the Dutch EEZ will require the relocating of military flying areas with forbidden access, while technical solutions such as “fill-in-the-gap” or relocation of lower airspace radars could unlock 10.25-18.16 GWs in the English EEZ. By avoiding high risk areas and prioritizing areas of low conflict, the bottlenecks, negative effects and inefficiencies related to space management options can be minimized, while synergies and positive effects of OWF deployment can be timely captured.